Negociação Brasil e China: seus principais aspectos culturais - Fernandes, Maria Fernanda Gomes (2008)
The dissertation aimed to analyze how is possible to minimize conflicts that arise during a negotiation between Chinese and Brazilians using the Jeswald Salacuse's model of cultural for as the mapping of potential outbreaks of conflict. It was considered necessary for this mapping to review the profile of the Chinese negotiator. This review took place through the completion of qualitative research to sixteen with Brazilian professionals from companies who trade with China. Through research could indicate which are the largest outbreaks of conflict in negotiating and pointing recommendations on how to avoid the appearance of these. At the end of this research were unable to verify that there were differences between the profile of Chinese negotiator pointed out in search of Salacuse and research conducted in this dissertation as well as make some recommendations for the Brazilian negotiators minimize the conflicts encountered when dealing with the new Chinese negotiator.